Transient Receptor Potential Cation Channel Subfamily V Member 1 Expression Promotes Chemoresistance in Non-Small-Cell Lung Cancer - Li, Li; Chen, Cheng; Xiang, Qin; Fan, Songqing; Xiao, Tian; Chen, Yangchao; Zheng, Duo (Frontiers in Oncology, 2022)
Approximately 85% of lung cancer cases are non-small-cell lung cancer (NSCLC). Chemoresistance is a leading cause of chemotherapy failure in NSCLC treatment. Transient receptor potential cation channel subfamily V, member 1 (TRPV1), a non-selective cation channel, plays multiple roles in tumorigenesis and tumor development, including tumor cell proliferation, death, and metastasis as well as the response to therapy. In this study, we found TRPV1 expression was increased in NSCLC. TRPV1 overexpression induced cisplatin (DDP) and fluorouracil (5-FU) resistance in A549 cells independent of its channel function. TRPV1 expression was upregulated in A549-DDP/5-FU resistant cells, and DDP/5-FU sensitivity was restored by TRPV1 knockdown. TRPV1 overexpression mediated DDP and 5-FU resistance by upregulation of ABCA5 drug transporter gene expression, thereby increasing drug efflux, enhancing homologous recombination (HR) DNA repair pathway to alleviate apoptosis and activating IL-8 signaling to promote cell survival. These findings demonstrate an essential role of TRPV1 in chemoresistance in NSCLC and implicate TRPV1 as a potential chemotherapeutic target.